2013
DOI: 10.1089/bio.2012.0051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinical Biomarkers for Pre-Analytical Quality Control of Blood Samples

Abstract: Background: Pre-analytical conditions are key factors in maintaining the high quality of biospecimens. They are necessary for accurate reproducibility of experiments in the field of biomarker discovery as well as achieving optimal specificity of laboratory tests for clinical diagnosis. In research at the National Biobank of Korea, we evaluated the impact of pre-analytical conditions on the stability of biobanked blood samples by measuring biochemical analytes commonly used in clinical laboratory tests. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
(30 reference statements)
0
27
0
7
Order By: Relevance
“…Particular critical analytes are ALAT, K, LD, and P, which in most studies are reported as stable only for a few hours at room temperature and above (up to 12 h depending on analyte and study) [4,8–10,12,15,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Particular critical analytes are ALAT, K, LD, and P, which in most studies are reported as stable only for a few hours at room temperature and above (up to 12 h depending on analyte and study) [4,8–10,12,15,19]. …”
Section: Discussionmentioning
confidence: 99%
“…These samples are obtained by centrifugation after anticoagulation (using an anticoagulant, such as EDTA or heparin) and coagulation of whole blood, respectively [4] . Currently, the delay between collection and whole-blood centrifugation can influence the concentrations of circulating blood components, including metabolites and cytokines, due to prolonged contact with cells 5 , 6 , 7 , 8 , 9 , 10 . Hemolysis, which results in the release of hemoglobin and other intracellular components from red blood cells, might also occur when whole-blood processing is delayed [11] .…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory tests (such as clinical biochemistry and hematology) routinely performed for diagnosis or prediction of prognosis in a clinical laboratory, the main causes of laboratory errors are preanalytical variables involved with biospecimen collection, processing, and storage conditions 12 , 13 , 14 . Several studies demonstrated that delayed whole-blood separation affects the plasma and serum concentrations of biochemical analytes [e.g., alanine aminotransferase (ALT), aspartate aminotransferase (AST), inorganic phosphorus (IP), potassium (K + ), and lactate dehydrogenase (LDH)] 6 , 7 , 8 , 9 . In this study, we investigated whether clinical-biochemistry analytes can be used to assess the delayed whole-blood separation.…”
Section: Introductionmentioning
confidence: 99%
“…PaxGene, Qiagen), may improve efficiencies at surgical/tissue collection sites. Considerable attention has been devoted to developing procedures for appropriate collection and optimum preservation methods including the time to preservation, sample sizes, fixation/ storage conditions and most recently, markers useful for assessing sample quality (6, 9-18). Such attention is reflected in the release of standard operating procedures (SOPs) by the National Cancer Institute Cancer Human Biobank (caHUB), which conducts tissue collection for The NIH Genotype-Tissue Expression (GTEx) Project (19).…”
Section: Introductionmentioning
confidence: 99%